Avaliação da assistência pré-natal de gestantes com risco habitual - Bernardo, Elizian Braga Rodrigues (2016)
It is an evaluative study conducted in order to evaluate the prenatal care offered to pregnant women with normal risk in a health-school service by evaluating its structure, process and results. The study was conducted from May 2015 to January 2016 at the Natural Birth Center Ligia Barros Costa, located in the district of Planalto do Pici, Fortaleza, Ceará. The sample totaled 554 records and 50 postpartum women who underwent prenatal on the Natural Birth Center. The data collection instrument contemplated sociodemographic, clinical and obstetric aspects and indicators of structure, process and result of prenatal assistance. The data were analyzed with the support of the Statistical Package for Social Sciences statistical software. The structure of the service was classified as adequate, with 30 (90.62%) of the indicators according with the ministerial recommendations. Process indicators were classified into three levels. Level I, referring to the number of medical appointment and the early initiation of prenatal care; Level II, referring to the level I added to the clinical and obstetric procedures; and Level III, referring to the level II added to the laboratory tests. Their respective indicators had resulted adequate in 92 (16.4%) cases of level I, in 86 (15.4%) cases of level II and in only 44 (7.9%) cases of level III. Of the 50 mothers interviewed, 46 (92%) were on Exclusive Breastfeeding, 46 (92%) delivered newborn with normal weight, 42 (84%) underwent postpartum consultation, 31 (62%) had normal birth, 41 (82%) had no complications during pregnancy and/or giving birth, none of them presented the case of congenital syphilis, vertical transmission of HIV or neonatal tetanus and 41 (82%) were satisfied with the performed prenatal care. Thus, the result of prenatal care was classified as adequate. Maternal and obstetric characteristics that were associated with statistical significance with the inadequate beginning of prenatal care were: pregnant women without a partner (p=0,013), absence of complications in previous pregnancies (p=0,004), previous birth (p <0,001), abortion history (p=0,009) and with children (p<0.001). The number of inadequate consultation was associated with multiparity (p=0.026), absence of complications during the current pregnancy (p <0.001) and previous birth (p=0.003). Already the inadequatecy of the realization of laboratory tests were associated with: women without a partner (p=0,021), with no family history of comorbidity (p <0,001) and first pregnancy (p=0,022). About the satisfaction with the received prenatal care, most mothers, 41 (82%) were satisfied, showing, through statistical association (p=0.039), that mothers who started early prenatal were 33% (95% CI: 1.10 – 1.61) more likely to be satisfied with prenatal care. Therefore, it is concluded that the service performance have adequated structure and results indicators. However, leaves something to be desired as to the suitability of the process indicators, deserving more attention from health managers and professionals for the planning of actions in order to improve these indicators.